THE ANTECEDENTS OF AN EFFECTIVE CITY BRANDING: A COMPREHENSIVE SYSTEMATIC REVIEW - Reimond Kowaas; Jeane Cicilia Syamsia; Deske W. Mandagi (SEAN Institute, 2023)
City branding has gained paramount importance as global cities vie for recognition and investment in an increasingly competitive landscape. Despite current city branding efforts focusing on superficial elements like logos and slogans, this study seeks a deeper understanding of the core drivers of successful city branding. Conducting a systematic literature review, the researchers meticulously screened and selected fifty scholarly papers from Scopus and Web of Science databases, adhering to inclusion criteria such as empirical research and publication date range no earlier than 2015. Through thematic analysis, the study identifies pivotal antecedents for effective city branding, encompass factors such as cultural identity and community engagement, environmental and natural elements, governance and safety, as well as infrastructure and services. Cultural heritage contributes to the city's unique identity, adding a dimension of authenticity. Community engagement fosters a sense of ownership among residents, infusing vitality into the brand narrative. Effective governance ensures coherence in the branding message. Infrastructure, serves as a foundational element, shaping the physical and functional attributes of the city. Tourism initiatives capitalize on the city's attractions, while strategic marketing shapes perceptions. Crucially, the study probes into the intricate interplay and collective influence of these diverse factors on the overall efficacy of city branding campaigns. Ultimately, the findings empower decision makers with informed insights, facilitating the cultivation of proficient city branding practices within the fiercely competitive urban landscape. By transcending superficial attributes and adeptly navigating complex interrelations, cities can craft resonant branding strategies, positioning themselves for success in the global arena.